Core muscle activity during physical fitness exercises - Oliva Lozano, José María (Henry Stewart Talks, 2022)
Core muscles and their activity, Core training, EMG activity, Free-weight exercises, Stability and traditional exercises, Physical fitness, Rectus abdominis, Internal and external obliques, Erector spinae, Lumbar multifidus, Transversus abdominis, Systematic review on core muscle activity